Assessment of teacher education and teaching resource use by students of a public University of Lima, and study of their academic performance - Llanos Castilla, José Luis (2015)
This research aimed to identify the relationship between the varia¬bles assessment of university teaching, teachers teaching resource use and academic performance which showed 112 college students who were on average 28.2 years old and attending the course Teaching General I of the Academic Professional School of Educa¬tion of a public university in Lima. The transaction method was not experimental, correlational, finding a significant positive correlation between the value of university education and academic achieve¬ment with 0.703 index relationship. The correlation between the value of university education, academic performance and assessing the use of educational resource with an index of 0.741 corrobo¬rated relationship. It is estimated that increasing the valuation of teacher teaching resource use, increase academic performance of students in this sample.